Phosphorylation-dependent immunomodulatory properties of B.PAT polysaccharide isolated from Bifidobacterium animalis ssp. animalis CCDM 218 - Pacyga-Prus, Katarzyna; Sandström, Corine; Šrůtková, Dagmar; Schwarzer, Martin; Górska, Sabina (Carbohydrate polymers, 2024)
A wide range of articles describe the role of different probiotics in the prevention or treatment of various diseases. However, currently, the focus is shifting from whole microorganisms to their easier-to-define components that can confer similar or stronger benefits on the host. Here, we aimed to describe polysaccharide B.PAT, which is a surface antigen isolated from Bifidobacterium animalis ssp. animalis CCDM 218 and to understand the relationship between its structure and function. For this reason, we determined its glycerol phosphate-substituted structure, which consists of glucose, galactose, and rhamnose residues creating the following repeating unit: To fully understand the role of glycerol phosphate substitution on the B.PAT function, we prepared the dephosphorylated counterpart (B.MAT) and tested their immunomodulatory properties. The results showed that the loss of glycerol phosphate increased the production of IL-6, IL-10, IL-12, and TNF-α in bone marrow dendritic cells alone and after treatment with Lacticaseibacillus rhamnosus GG. Further studies indicated that dephosphorylation can enhance B.PAT properties to suppress IL-1β-induced inflammatory response in Caco-2 and HT-29 cells. Thus, we suggest that further investigation of B.PAT and B.MAT may reveal distinct functionalities that can be exploited in the treatment of various diseases and may constitute an alternative to probiotics.
Keywords: Animals; Polysaccharides, Bacterial; Probiotics; Bifidobacterium; Cytokines; Dendritic Cells; Dephosphorylation; dendritické buňky; cytokiny; Caco-2 buňky; imunologické faktory; lidé; Mice; Immunomodulation; myši; bakteriální polysacharidy; Immunologic Factors; fosforylace; probiotika; Surface antigens; zvířata; HT29 Cells; Postbiotics; Bifidobacterium animalis; Lacticaseibacillus rhamnosus; Caco-2 Cells; Polysaccharides; buňky HT-29; Phosphorylation; Humans